Sistem Pendukung Keputusan Kelompok untuk Penilaian Kinerja Unit Perusahaan Menggunakan Metode PROMETHEE II dan Borda (Studi Kasus: Perum Jasa Tirta 1 Malang) - Dhea Azahria Mawarni; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Assessment of unit performance of the company aims to facilitate in evaluating the performance of each unit. Poor performance will have an impact on the quality of the company, so it needs to be improved and upgraded. However, the assessment of company unit performance in PJT 1 Malang is less efficient due to the absence of a system to process KPI Unit assessment data. This has an impact on the amount of manpower and required time in the assessment of the company's unit performance. To overcome these problems, it requires a computer system in the form of group decision support system (SPKK) to assist in the assessment of the company's unit performance. One method of Multi Criteria Decision Making is PROMETHEE II, used for decision making in every decision maker (DM). While Borda is used for the voting method. This study uses 72 alternative data and five assessment criteria. Based on the results of the weight test analysis, the best accuracy was obtained in the 3rd, 4th, and 5th experiments at the level of importance of the fourth weight with value of 83.3333% using the first range. And the highest accuracy based on the results of the amount of data test analysis obtained of 86, 1111% when using 36 data test.